Pengaruh Terapi Guided Imagery terhadap Kecemasan Pasien Gagal Ginjal Kronis yang Menjalani Hemodialisis: Quasi Eksperimen - Surya, Defrima Oka; Desnita, Ria; Setiawan, Ridwan (Poltekkes Kemenkes Bandung, 2026)
Background: Patients undergoing hemodialysis often experience high levels of anxiety, which negatively impacts their quality of life and adherence to treatment. Guided imagery therapy, as a mind-body relaxation technique, can reduce anxiety. Objective: This study aimed to evaluate the effectiveness of guided imagery therapy in reducing anxiety in patients with chronic kidney disease undergoing hemodialysis. Methods: This study used a quasi-experimental design with a control group. A total of 32 patients were recruited and randomly divided into the intervention group (n=16), who received guided imagery therapy for three times a week for one week, and the control group (n=16), who received standard care. The level of anxiety was measured using the State-Trait Anxiety Inventory (STAI) before and after the intervention. Descriptive statistics were used to analyze participant characteristics, and paired t-tests were used to evaluate changes in anxiety scores. Results: The research results showed that the pre-test data of both groups indicate a high level of anxiety. The average anxiety score in the intervention group before the intervention was 56.20, and after the intervention was 41.13. The average anxiety score in the control group before the intervention was 45.88, and after the intervention was 44.56. Bivariate results showed a significant decrease in anxiety scores after the intervention in the intervention group compared to the control group (p<0.05). Conclusion: Guided imagery therapy can significantly reduce anxiety levels in patients undergoing hemodialysis. This technique can be easily integrated into routine hemodialysis care as a complementary approach to enhance patients' psychological well-being.